Hantavirus transmission risk in function of climate and landscape structure - Prist, Paula Ribeiro (2016)
Hantavirus Cardiopulmonary Syndrome (HCPS) is a disease caused by Hantavirus, which are negative-sense RNA viruses in the family Bunyaviridae. These viruses are highly virulent to humans, taking about 50% of infected people to death. The main Hantavirus reservoir is constituded by generalist rodents species, which increase in abundance in agricultural and fragmented landscapes, potencially augmenting the transmission risk of the disease. Climate can also affect rodent population dynamics and the virus survival in the environment, as well as the time it remains virulent, while social factors may regulate the processes of transmitting viruses from reservoirs to humans. However, despite the high virulence of these viruses and the lack of vaccine is not yet well established how these different factors linked to landscape structure, climate and social conditions affect the dynamics of transmission of the disease. Thus, this study aimed to: 1) identify which social and ecological factors affect the transmission of HCPS, identifying the areas of greatest risk in the state of São Paulo and 2) predict how climate change (RCP4.5 and RCP8.5) and expansion of sugarcane scenarios influence the transmission of HCPS. To answer these questions the study system corresponded to the 645 municipalities that compose the state of São Paulo. To achieve our goals, in a first chapter, we conducted a literature review to understand how landscape structure and climate variables affect the risk of HCPS. In a second chapter we used a Bayesian model to quantify the association between HCPS annual incidence in the state of São Paulo, obtained by the number of cases confirmed by the Ministry of Health, between the years 1993-2012, and climate variables (total annual precipitation and mean annual temperature), landscape structure (percentage of native vegetation, number of fragments and percentage of area occupied with sugarcane), chosen in the literature review, and social factors (number of rural men over 14 years - risk population, and the Human Development Index - HDI). We build separate models for the Atlantic Forest and the Cerrado. In both biomes, the risk of HCPS increased mainly with the proportion of land cultivated with sugarcane and the HDI, but the proportion of native habitat, mean annual temperatures and risk population also showed positive relationships to Atlantic Forest. The average risk of HCPS for the state of São Paulo was 1.3%, with 6% of the municipalities being classified as medium to high risk (>= 5%). In a third chapter we used sugarcane expansion and extracted temperature anomalies of RCP4.5 and RCP8.5 scenarios of general circulation models (GCMs) of IPCC5 to predict HCPS risk. With sugarcane expansion, average risk for HCPS increases from 1.3 to 1.5%, while RCP4.5 and RCP8.5 scenarios increased the risk to 1.6% and 1.7%, respectively. RCP4.5 and RCP8.5 scenarios alone are responsible for the largest increase in the maximum risk of infection (46.1% to 51.4% and 51.7%), while the sugarcane expansion combined with climate scenarios are causing the larger expansion in the number of municipalities at high risk, which goes to 7%. Our analyzes provide the first evidence on the action of landscape, climate and social factors in HCPS incidence in the Neotropics. Moreover, our risk maps can be used to optimize the correct allocation of resources, allowing actions to be taken to reduce the impacts of sugarcane expansion and climate change over this disease propagation